2016
DOI: 10.1371/journal.pone.0156702
|View full text |Cite
|
Sign up to set email alerts
|

NFKB1 Promoter DNA from nt+402 to nt+99 Is Hypomethylated in Different Human Immune Cells

Abstract: Sepsis, with a persistently high 90-day mortality of about 46%, is the third most frequent cause of death in intensive care units worldwide. Further understanding of the inflammatory signaling pathways occurring in sepsis is important for new efficient treatment options. Key regulator of the inflammatory response is the transcription factor NFκB. As we have recently shown, the -94 Ins/Del NFKB1 promoter polymorphism influences sepsis mortality. However, a molecular explanation is still missing. Thus, promoter … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…The minimum sample size for detecting the group differences in the percent increase in NFKB1 and NFKB2 methylation at α = 0.05 (two-sided) and (1-β) = 0.8, determined using an unpaired t-test, was 4 and 6 for each group, respectively, which is smaller than the sample size in the present study. Because methylation of promoter regions is associated with transcriptional suppression of the corresponding gene, enhanced methylation in NFKB1 and NFKB2 for the HD group suggests reduced NFKB1 and NFKB2 gene expression [ 33 , 34 ].…”
Section: Resultsmentioning
confidence: 99%
“…The minimum sample size for detecting the group differences in the percent increase in NFKB1 and NFKB2 methylation at α = 0.05 (two-sided) and (1-β) = 0.8, determined using an unpaired t-test, was 4 and 6 for each group, respectively, which is smaller than the sample size in the present study. Because methylation of promoter regions is associated with transcriptional suppression of the corresponding gene, enhanced methylation in NFKB1 and NFKB2 for the HD group suggests reduced NFKB1 and NFKB2 gene expression [ 33 , 34 ].…”
Section: Resultsmentioning
confidence: 99%
“…The NF-κB signaling pathway plays an important role in the inflammatory response and macrophage polarization. A growing body of evidence showed that the NF-κB signaling pathway can be regulated by DNA methylation [47,48]. In germinal center B cells, elevated DNMT1 expression causes hypomethylation of the promoter of the nuclear factor kappa B kinase subunit epsilon ( IKBKE ) inhibitor, which is one of the NF-κB pathway signaling components that induces IKB phosphorylation [47].…”
Section: Discussionmentioning
confidence: 99%
“…They play an important role in the inflammatory response and macrophage polarization. A growing body of evidence showed that the two signaling pathways can both be regulated through DNA methylation ( 35 , 36 ).…”
Section: Discussionmentioning
confidence: 99%